ANALYSE DER SCHREIBAUFGABEN IM LEHWERK NETZWERK A1 - Arkan Luqman Khairynanto, - (2020)
ABSTRACT Khairynanto, Arkan Luqman, 2020. Analysis of Writing Tasks in The Textbook Netzwerk A1. Bandung. A thesis at the German Department. Educational Faculty of Languages and Literature. Indonesia University of Education. German is one of the foreign language that is learned and taught in Indonesia, particularly in some institutions such as school, language school, college and university. There are four aspects that affect German proficiency, they are listening comprehension, speaking comprehension, reading comprehension and writing comprehension. The german learner must have a good proficiency in those four aspects. This study is focusing only on the writing comprehension. In Indonesia, many german learners use the textbook Netzwerk A1, especially the students of the German Major in the Educational University of Indonesia in the first semester. This textbook consists of the course book and the exercise book. In this textbook there are a lot of writing exercises. Yet not every chapter has writing exercise. The purpose of this research is to find out: 1) the suitability of the writing exercises in the text book Netzwerk A1 compares to the Common European Framework of Reference for Languages (CEFR), and 2) the type of the writing exercise in the textbook Netzwerk A1. The results are as follows: 1) There are 15 writing exercises in the course book Netzwerk A1 and 23 writing exercises in the exercise book Netzwerk A1 and 9 writing exercises in the course book are suitable to level A1, 5 writings exercises to level A2 and one writing excercise to level B1. And in the exercise book Netzwerk A1, 8 writing excercises are suitable for level A1, 12 writing excercises suitable for level A2, 2 writing excercises for level B1 and one writing excercise for level B2. 2) In the course book Netzwerk A1 there are 7 writing excercises that count as Formulieren and 10 writing excercises that count as Planen und Formulieren. In the exercise book Neztwerk A1 there are 13 writings excercises that count as Formulieren and 10 writing excercises that count as Planen und Formulieren. It is highly recommended that a writing task consists of 3 phases of excercise type, which are Planen, Formulieren, and Überarbeiten, so ones writing skill can be effectively supported. That is why teachers need to provide the writing excerscises with 3 excerscise types. Keywords: CEFR, course book Netzwerk A1, exercise book Netzwerk A1, exercise type, writing excercise